Uji Aktivitas Antioksidan menggunakan Metode DPPH (2,2-Difenil-1-Pikrilhidrazil) Terhadap Ekstrak Daun Kunyit (Curcuma domestica) - Khanna Hadirama; Rendy Wikrama Wardana; Euis Wikrama Nursa’adah; Aceng Wikrama Ruyani; M. Lutfi Firdaus (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aimed to identify the antioxidant content in turmeric leaf extract using the DPPH (2,2-diphenyl-1-picrylhydrazyl) method. The tested concentrations include 200 ppm, 150 ppm, 100 ppm, 50 ppm, 25 ppm, and 12.5 ppm, with absorbance measurements conducted using a UV-Vis Spectrophotometer. Data were analyzed by calculating the percentage of antioxidant activity based on the absorbance values of each concentration. Subsequently, the IC50 value was determined using a nonlinear regression equation, representing the relationship between the logarithm of concentration and the percentage of antioxidant activity (inhibition). The results of the study showed that the IC50 value of turmeric leaf extract was 61.88. The conclusion of this study indicates that turmeric leaf extract exhibits strong antioxidant activity. Keywords: Antioxidant, Turmeric Leaves, DPPH, IC50